EKSISTENSI PENDIDIKAN DALAM MEMBANGUN MORALITAS BANGSA - Drs. H Firdaus (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2016)
At the level of values, education has a vital role as a driver of the individual and the community to achieve progressivity in all aspects of life. In addition, education can be a determinant, it is important for personal and social transformation process. And indeed it is the ideals of education that promote their empowerment. Education is an attempt to increase proficiency, skills, understanding and attitudes through learning and experience needed to allow humans to maintain and continue living and to achieve the goal of his life. Building a nation's character is a central issue and a national issue. There are three reasons that make the nation's character becomes important. First, the nation experienced a developmental stage that is affected by global life and is known as the era of the information which influence the social order. Secondly, in terms of mentality, Indonesia still needs to clean up its act. Third, the same information age, this nation entered the era of reform that brings a very drastic change.